2005
DOI: 10.1152/ajpendo.00325.2004
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I downregulates resistin gene expression and protein secretion

Abstract: Chen, Yen-Hang, Pei-Fang Hung, and Yung-Hsi Kao. IGF-I downregulates resistin gene expression and protein secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 52 publications
6
31
0
1
Order By: Relevance
“…It has been shown that insulin upgrades leptin expression (Barr et al 1997) and downgrades resistin expression (Haugen et al 2001, Shojima et al 2002, Chen et al 2005. But the acute effects we observed are likely resulting from facilitation of regulated vesicular secretion of pre-stored adipokines instead of increased protein synthesis.…”
Section: Discussionmentioning
confidence: 69%
“…It has been shown that insulin upgrades leptin expression (Barr et al 1997) and downgrades resistin expression (Haugen et al 2001, Shojima et al 2002, Chen et al 2005. But the acute effects we observed are likely resulting from facilitation of regulated vesicular secretion of pre-stored adipokines instead of increased protein synthesis.…”
Section: Discussionmentioning
confidence: 69%
“…The medium was then changed to DMEM containing 10% FBS for an additional 6 -10 days (replaced every other day). With this protocol, Ͼ90% adipocyte differentiation was achieved, as indicated by phenotypic appearance and triglyceride accumulation (10). Differentiated adipocytes expressed more Rstn mRNA than did preadipocytes or differentiating preadipocytes (10,44).…”
Section: Methodsmentioning
confidence: 99%
“…Acti-D (5 g/ml) and CHX (5 g/ml) were used to block transcriptional and translational activities, respectively (10,22). In experiments, 3T3-L1 adipocytes were pretreated with and without either Acti-D for 30 min or CHX for 90 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, treatment with resistin causes glucose intolerance (10). Resistin is regulated by cytokines, including endothelin, insulin, insulin-like growth factors and peroxisome proliferator-activated receptor γ (11,12). In rodents, resistin is located within adipocytes, while human resistin is primarily expressed in macrophages and neutrophils (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%